Ekspor Teh Hitam Indonesia ke Jepang: Struktur Pasar dan Daya Saing: Indonesian Black Tea Export to Japan: Market Structure and Competitiveness - Fikri Aldi Dwi Putro; Nia Kurniawati Hidayat (National Research and Innovation Agency, 2023)
Indonesian tea export to international market is dominated by black tea. Japan becomes the black tea export destination with big untapped export potential, but has volatile export value, thus hinders the optimization of black tea export potential to Japan. This study aims to analyze the market structure and competitiveness as well as determine the Indonesian black tea market expansion to Japan. This study employs Herfindahl-Hirschman Index (HHI), Concentration Ratio (CR4), Revealed Comparative Advantage (RCA), Revealed Symmetric Comparative Advantage (RSCA), Export Product Dynamic (EPD), and X-Model Potential Export Products. The results show that the packaged and bulk black tea market structure in Japan is oligopoly. Indonesian bulk black tea gains comparative advantage, whereas Indonesian packaged black tea lacks comparative advantage in Japan market. Besides that, Indonesian bulk black tea has stronger competitive advantage over Indonesian packaged black tea. Furthermore, Indonesian bulk black tea is able to become the focus of export expansion to Japan at the moment.